Aids en kunst : [Hoe artistiek is Aids : de gevreesde ziekte en de schone kunsten) - Schutte, Xandra; Sanders, Stephan; Raddatz, Fritz J. (Amsterdam : De Groene Amsterdammer, 1993)
Fonds Suzan Daniel (FSD)
In: De Groene Amsterdammer, 117(1993)42
Nederlands
Monografie